STUDENT BUSINESS CENTER AS A MEANS OF DEVELOPING ENTREPRENEURSHIP CAPACITY FOR STUDENTS - Devi Rachmasari (Politeknik Ubaya, 2017)
Entrepreneurs obviously play significant role in the growth of economics as it canbe seen in the industrial countries which have more than 10% entrepreneurs oftheir population. Indeed, the role of universities in preparing the society, especiallytheir graduation to be self-employed, to be an entrepreneur is surely substantial.Entrepreneurship education is the answer in maximizing students’ capacity onknowledge as well as skill to be entrepreneurs. Many studies indicate the positiveimpact of entrepreneurship education. This paper will discuss entrepreneurshipeducation in Politeknik Ubaya especially through Student Business Center, a placewhere students are able to practice what they have learned in the classroom